2019
DOI: 10.1007/s42770-019-00116-z
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of LAMP-coupled lateral flow device for the detection of MAP in livestock at point of care resource-limited areas

Abstract: The Mycobacterium avium subspecies paratuberculosis (MAP) causes paratuberculosis (Johne's disease), a systemic and chronic inflammation of intestine that affects bovine, small ruminants like goat and sheep. The disease has a greater economic importance in cattle and in small ruminants. But its effective control is impeded due to lack of rapid and accurate diagnostics. The present study is aimed at developing a LAMP-coupled lateral flow device (LFD) for rapid detection of paratuberculosis in livestock animal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…These difficulties mean that alternative, more rapid detection methods for mycobacteria are often used. PCR has proven to be a powerful tool for the specific detection of mycobacterial signature DNA sequences from a variety of sample matrices (Dinnes et al, 2007;Priyadarshini et al, 2017), and most recently loop-mediated isothermal amplification (LAMP) methods have been successfully developed for the specific detection of MAP (Punati et al, 2019). However, when used as a diagnostic test, efficient release of DNA is crucial for the success of any PCR or nucleic acid-based method, especially when this is being used to quantify the number of cells present in a sample.…”
Section: Introductionmentioning
confidence: 99%
“…These difficulties mean that alternative, more rapid detection methods for mycobacteria are often used. PCR has proven to be a powerful tool for the specific detection of mycobacterial signature DNA sequences from a variety of sample matrices (Dinnes et al, 2007;Priyadarshini et al, 2017), and most recently loop-mediated isothermal amplification (LAMP) methods have been successfully developed for the specific detection of MAP (Punati et al, 2019). However, when used as a diagnostic test, efficient release of DNA is crucial for the success of any PCR or nucleic acid-based method, especially when this is being used to quantify the number of cells present in a sample.…”
Section: Introductionmentioning
confidence: 99%
“…In 53.33% (n = 16) of studies, more than one detection method was used. In 16.66% (n = 5) of studies, combination of three methods was used while in only two studies (6.66%), combination of four different methods was reported ( 17 , 18 ).…”
Section: Resultsmentioning
confidence: 99%
“…In 53.33% (n = 16) of studies, more than one detection method was used. In 16.66% (n = 5) of studies, combination of three methods was used while in only two studies (6.66%), combination of four different methods was reported (17,18). Among all the eligible studies, 4 studies showed 100% sensitivity, while for 16 studies this parameter was higher than 90%.…”
Section: Study Characteristics and Meta-analysismentioning
confidence: 99%
“…Furthermore, it is simpler to perform, and merely use constant-temperature equipment, such as a water bath or Mini Dry Bath within 60 min. This can be potentially used for tests in the field (Punati et al, 2019;Joon et al, 2019;Tumino et al, 2020). In addition, LAMP has been extensively applied in food-borne pathogens, allergens, and genetically modified organisms in food analysis (Hara-Kudo et al, 2010;Rostamkhani et al, 2011;Saharan et al, 2015;Shi et al, 2017;Yuan et al, 2018;Li et al, 2019;Zhuo et al, 2019;Tumino et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, LAMP has been extensively applied in food-borne pathogens, allergens, and genetically modified organisms in food analysis (Hara-Kudo et al, 2010;Rostamkhani et al, 2011;Saharan et al, 2015;Shi et al, 2017;Yuan et al, 2018;Li et al, 2019;Zhuo et al, 2019;Tumino et al, 2020). Furthermore, LAMP products traditionally observed by gel electrophoresis and hydroxynaphthol blue (HNB) or SYBR are either difficult to distinguish by fluorescent dyes, which need special equipment and the process is time-consuming, or easily exposed to aerosol pollution due to the opening of the lid (Shi et al, 2017;Punati et al, 2019;Zhang et al, 2019). Moreover, the amplified products are visualized directly on an LFD with one or two bands, which is more suitable for on-site detection (Shi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%